A poética imaginária do videogame: as passagens e as traduções do imaginário e dos mitos gregos no processo de criação de jogos digitais - Gasi, Flávia Tavares (2012)
The attendant research has as its main objective to comprehend how imaginary figures and Greek myths are transported to creative process of games storytelling. This study is a review of some concepts such as: imaginary, Greek myths, in-game ludology and narratives. The next step is a case study proposal of three games, each of them translating the imaginary figure in a different way: the first one demonstrates narrative and mythological images from Greece appearing almost exactly the same and fits in action genre (God of War frachise); the second one proposes a storytelling that merges contemporaneous imaginary figures, and belongs to FPS genre First Person Shooter (Bioshock); and the last and third one recreates the essence of imaginary figures through the narrative and characters, however, it s not made literally, and fits Role Playing genre RPG (Eternal Sonata). For its theoretical ground the research is supported by Gaston Bachelard, Gilbert Durand, Joseph Campbell; the translation point of view is approached considering Julio Plaza´s research; and the concepts of imaginagy in the creative process are based on Lucia Leão´s writings. For the theoretical point of view of ludology, we will look through the writings of authors Turkle and Landow. This research focus on the comprehension of the creative process, narrative and ludology from the imaginary and myths point of view. Therefore, we will investigated from an archeological perspective and understand the passages of archetypical figures in game narrative